Strained germanium for applications in spintronics (Phys. Status Solidi A 11∕2016). Issue 11 (15th November 2016) - Morrison, Christopher; Myronov, Maksym
Abstract : Germanium (Ge) is another group–IV semiconductor material which recently started attracting tremendous attention in spintronics following the success of silicon (Si). The crystal inversion symmetry of Si and Ge precludes the spin relaxation of conduction electrons by the Dyakonov–Perel mechanism, resulting in a long spin relaxation time. Since the proposal of the spin FET in 1990 by Datta and Das, semiconductor materials have been studied for their spin–orbit (S–O) interactions, particularly those that can be modified by an applied electric field, such as the Rashba S–O interaction, in order to create devices that utilise spin modulation and control to perform logic operations. Since then new proposals have appeared. Nowadays they include spin transistors with several different operating principles, spin–based diodes, spin–based field programmable gate arrays, dynamic spin–logic circuits, spinonly logic, spin communication and others. In the review by Morrison and Myronov (pp.2809–2819 ), the focus is made on presenting progress in Ge spintronics including recent key advances.